Kajian Kritis Tentang Jiwa (An-Nafs) dalam Pemikiran Islam (Perspektif Pendidikan Islam) - Ramli, Ramli; Harun, Hamzah; Aderus, Andi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to find out the essence of An-Nafs based on Islamic thought and explain An-Nafs and Islamic Education according to the interpretation of Islamic philosophers or thinkers. This research is carried out through a qualitative approach with a literature study approach. The preparation of the article is carried out by examining various sources that are directly related to the focus of this research. The main sources of research data are reference books and research articles published in various scientific journals and indexed by google scholar. Data collection was carried out using the keyword